The female sex pheromone (Z)-4-undecenal mediates flight attraction and courtship in Drosophila melanogaster. (February 2022) - Borrero-Echeverry, Felipe; Solum, Marit; Trona, Federica; Becher, Paul G.; Wallin, Erika A.; Bengtsson, Marie; Witzgall, Peter; Lebreton, Sebastien
Graphical abstract: Highlights: The female-produced D . melanogaster pheromone Z4-11Al attracts males and females. Z4-11Al elicits, in addition, courtship in experienced D . melanogaster males. Z4-11Al and male pheromone cVA interact with vinegar sex-specifically. Functional imaging corroborates that Z4-11Al is perceived via DmelOr69a. Abstract: Specific mate communication and recognition underlies reproduction and hence speciation. Our study provides new insights in Drosophila melanogaster premating olfactory communication. Mate communication evolves during adaptation to ecological niches and makes use of social signals and habitat cues. Female-produced, species-specific volatile pheromone ( Z )-4-undecenal ( Z 4-11Al) and male pheromone ( Z )-11-octadecenyl acetate (cVA) interact with food odour in a sex-specific manner. Furthermore, Z 4-11Al, which mediates upwind flight attraction in both sexes, also elicits courtship in experienced males. Two isoforms of the olfactory receptor Or69a are co-expressed in the same olfactory sensory neurons. Z 4-11Al is perceived via Or69aB, while the food odorant ( R )-linalool is a main ligand for the other variant, Or69aA. However, only Z 4-11Al mediates courtship in experienced males, not ( R )-linalool. Behavioural discrimination is reflected by calcium imaging of the antennal lobe, showing distinct glomerular activation patterns by these two compounds. Male sex pheromone cVA is known to affect male and female courtship at close range, but does not elicit upwind flight attraction as a single compound, in contrast to Z 4-11Al. A blend of the food odour vinegar and cVA attracted females, while a blend of vinegar and female pheromone Z 4-11Al attracted males, instead. Sex-specific upwind flight attraction to blends of food volatiles and male and female pheromone, respectively, adds a new element to Drosophila olfactory premating communication and is an unambiguous paradigm for identifying the behaviourally active components, towards a more complete concept of food-pheromone odour objects.